The male-focused marital relationship enrichment and sexual well-being interventions: A scoping review - Solmaz Abdollahzadeh Sardehaei; Effat Merghati Khoei; Beheshteh Niusha; Zahed Rezaei (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: There is an increasing need for sexual well-being and health promotion strategies that effectively engage men. Researchers have evaluated the efficacy of sexual and reproductive health-related and marital enhancement interventions in male-dominated societies. However, few have focused on culturally appropriate and gender-specific program effects. Objective: This review aims to evaluate evidence of existing interventions aimed at enriching marital relationships and sexual well-being in adult men. Materials and Methods: This scoping review was conducted by searching various databases (CINAHL, PsycINFO, EMBASE, Google Scholar, PubMed, Scopus, SID, and Noormags), and other available resources in both English and Persian languages. We located all publications up to January 2023 with no time restriction. Inclusion criteria were studies targeting men in the enrichment of marital and sexual relationships, which focus on marital/sexual enrichment, sexual and reproductive health (SRH) program, passionate relationship, or sexual satisfaction as the main outcomes. PRISMA guidelines were utilized in this review. Results: Of records 34,405 retrieved by searching, after removing duplicate articles, 8 articles were included based on the inclusion criteria. SRH program was the main focus of 6 articles. Marital and sexual enhancement were common areas of focus in 2 studies. Research methods included 2 semi-experimental, 3 clinical trials, 1 systematic review, 1 content analysis, and a mixed method. According to the assessment result, 4 articles were moderate and 4 were of high quality. Conclusion: Our findings reveal that a small number of interventions specifically offering SRH or marital and sexual enhancement programs to men should be conducted. As the majority were heterosexual couples, we recommend male-focused programs recognizing men's sexuality.